PSYCHOSOCIAL BURDEN OF PARENTS HAVING CHILDREN WITH HAEMOPHILIA IN NEPAL - Shakya, Milashree; Shila Banstola, Ratna; Shrestha, Romina (Journal of Chitwan Medical College, 2024)
Background: Parenting a child with haemophilia, a hereditary bleeding disorder, causes more stress than parenting a normal child. The main aim of this study was to find out the psychosocial burden faced by parents having children with haemophilia in Nepal. Methods: In this cross-sectional study, 76 parents having children with haemophilia were recruited from Nepal Haemophilia Society using a non-probability purposive sampling technique. The Zarit Burden Interview scale was used. Chi-square test and odds ratio at 95% confidence interval were used to assess an association between parents’ psychosocial burden with the parents and child-related variables using SPSS version 16. Results: A moderate level of psychosocial burden was prevalent among 60.5% of the parents. There was a significant association between parents’ psychosocial burden with parents’ education (p = 0.037), income (p = 0.03), type of Haemophilia among children (p = 0.03) and type of treatment received by children (p = 0.01). Further, the odds ratio predicted that psychosocial burden was 3.0 times higher (95% CI = 1.1 – 8.3, p = 0.04) among those parents with insufficient income and 4.2 times higher (95% CI = 1.3 – 13.4, p = 0.02) for the parents whose children were under factor VIII and associated treatment. Conclusions: Psychosocial burden, particularly of moderate intensity was higher in parents having children with haemophilia. Those parents with low education level, with less income and whose children are diagnosed with Haemophilia A and under factor VIII and associated treatment should be more considered in reducing their psychosocial burden.